A Study of India's Textile Exports and Environmental Regulations (Springer Singapore, 2018)
This book examines the interplay between trade and the environment, with a focus on the Indian textile sector. While it is often claimed that developed countries' non-tariff trade measures adversely affect the trade prospects of developing countries, establishing that claim systematically is a challenging task. This book examines the dilemma on the basis of various approaches, including a primary survey of different stakeholders and the large-scale modelling of the economy-environment inter-linkages. The interplay between the costs involved in meeting environmental regulations and the potential price-premiums that the cleaner products would get in the international market is analysed in order to assess the future trade prospects for Indian textiles. In addition, the book provides a comprehensive overview of the present scenario of the Indian textile sector. Accordingly, it will be of great interest to researchers, policy makers and graduate students specializing in environmental economics, development economics and international economics.